Self-esteem, Islamic Behavior, and Writing Assessment for Indonesian Language Madrasa Teachers: An Empirical Phenomenological Investigation - Desi Sukenti; Agustina; Ahmad Fauzan (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
Improving students' academic achievement in Indonesian language studies at madrasas requires effective writing evaluations. This study explores how Islamic behavior and self-esteem attribution among Indonesian language teachers at Madrasas influence their approach to creating writing assessments using a phenomenological method. Through in-depth interviews with twenty teachers, the thematic analysis revealed that teachers' Islamic values provide a religious framework that shapes their understanding and application of assessment development. Teachers' evaluations incorporate moral and religious principles, reflecting on their self-worth and the intrinsic value of students' written work. Islamic behavior and the attribution of self-esteem enhance teachers' commitment to fair, reflective assessments, which ultimately support students' literacy and academic growth. The study suggests that embedding Islamic behavior and self-esteem attribution in writing assessments strengthens teacher development and student success in Indonesian language studies. Future studies could further explore the role of these factors in teacher preparation and assessment practices in Indonesian madrasas.